SECURITY OF LIVES, RIGHTS TO PEACEFUL ASSEMBLY AND THE ENDSARS PROTEST IN NIGERIA - Olufunmilayo Oyelude; Oyedamade Opakunbi; Jacob Babajide; Jude Ilodibe (International Studies Journal)
Every country has a constitution, in which human rights are enshrined, but it appears that even with the constitution stipulating such rights; human rights are still questionable. This study investigated Human security and the rights to peaceful assembly and association, the study evaluated the combined effect of constitutional human rights on the security of lives in Nigeria. The study adopted a descriptive survey design of ex-post-facto to provide a relevant and accurate explanation at one or more points in time. The Snowball sampling technique was used to select 100 identified participants of the End SARS protest. Data obtained were analysed using both descriptive and inferential statistics of the Statistical Package for Social Sciences (SPSS) version 23.0. The findings revealed that the constitutional right to freedom of expression has a positive effect on the security of lives in Nigeria (Beta=.968, t=37.436, p